The Implementation of ChatGPT-based Learning for Higher Education in Indonesia: Systematic Literature Review - Sulfaedah Lestari (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research investigates the implementation of ChatGPT-based learning in higher education in Indonesia, emphasizing the analysis of its technical aspects and their contribution to educational practices. Through a systematic literature review, this study examines the positive impacts and challenges of integrating ChatGPT in university settings, drawing on recent analyses and diverse scholarly sources. The data were obtained from a variety of academic databases, including reputable web-blogs, Google Scholar, the Indonesian National Library's database, Education Resources Education Center (ERIC) Database, and E-Resources Perpusnas. The findings reveal that ChatGPT significantly enhances student engagement and writing skills, particularly in English as a Foreign Language (EFL) contexts. Key features such as custom GPTs, prompt engineering, and personalized settings play a crucial role in maximizing the tool's educational benefits. This research underscores the potential of ChatGPT to transform learning experiences by fostering interactive, personalized, and efficient educational environments. The implications of these findings contribute to a deeper understanding of AI's role in education, highlighting its capacity to enhance learning outcomes and educational engagement in higher education institutions in Indonesia.